2017
DOI: 10.5344/ajev.2017.16119
|View full text |Cite
|
Sign up to set email alerts
|

Release of Biologically Active Peptides from Grape Juice by Oenococcus oeni Isolated from Argentine Wine

Abstract: The increase in biologically active peptides after proteolytic activity of Oenococcus oeni X 2 L was studied in grape juice medium (GJM) and in GJM fermented with Saccharomyces cerevisiae mc2. Sequential inoculation of O. oeni X 2 L with proteolytic activity in GJM before ("I" medium) and after ("F" medium) yeast fermentation allowed peptide release. In the "I" medium, bacterial proteolytic activity (0.083 mM) released 3.88 mg nitrogen (N) of peptides per liter and produced an increase of 203.39 µmol/L in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…oeni resulted in a significant increase compared to grape juice fermented only by O. oeni . The authors demonstrated that the proteolytic system of O.…”
Section: Peptides In Brewed Winesmentioning
confidence: 93%
See 2 more Smart Citations
“…oeni resulted in a significant increase compared to grape juice fermented only by O. oeni . The authors demonstrated that the proteolytic system of O.…”
Section: Peptides In Brewed Winesmentioning
confidence: 93%
“…76 Yeast autolysis further increased the peptide concentration and enhanced the ACEI activity 15,77 and antioxidant effects. 77 However, some studies reported that O. oeni can also use proteins in grape juice 78 and wine medium 79,80 78 The authors demonstrated that the proteolytic system of O. oeni contributed to release bioactive peptides after yeast fermentation. The impact of O. oeni on peptides in wine has two aspects: using peptides as the nitrogen source and releasing peptides by its own proteolytic system.…”
Section: ■ Peptides In Brewed Winesmentioning
confidence: 99%
See 1 more Smart Citation